2017
DOI: 10.1039/c7ta04834c
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-filled bacterial nanocellulose as a biodegradable interfacial photothermal evaporator for highly efficient solar steam generation

Abstract: A flexible, scalable and completely biodegradable photothermal evaporator for highly efficient solar steam generation is fabricatedvia in situloading polydopamine particles in bacterial nanocellulose matrix during its growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(146 citation statements)
references
References 64 publications
1
145
0
Order By: Relevance
“…Wang et al (2016b) studied photothermal CNT-based materials and reported a solar thermal conversion efficiency of as high as 82% with bilayered CNT-silica materials. Polymers such as polydopamine was pioneered as a biodegradable PTM (Jiang et al, 2017). Organic polymers such as polypyrrole (Zhang et al, 2015a), polyaniline (PANI) (Huang et al, 2015a), and poly(1,3,5hexahydro-1,3,5-triazine) (Chen et al, 2018) have been explored for their photothermal properties.…”
Section: Photothermal Conversion Materials and Their Propertiesmentioning
confidence: 99%
“…Wang et al (2016b) studied photothermal CNT-based materials and reported a solar thermal conversion efficiency of as high as 82% with bilayered CNT-silica materials. Polymers such as polydopamine was pioneered as a biodegradable PTM (Jiang et al, 2017). Organic polymers such as polypyrrole (Zhang et al, 2015a), polyaniline (PANI) (Huang et al, 2015a), and poly(1,3,5hexahydro-1,3,5-triazine) (Chen et al, 2018) have been explored for their photothermal properties.…”
Section: Photothermal Conversion Materials and Their Propertiesmentioning
confidence: 99%
“…This indicated that the CNFAs effectively suppressed light reflection and improved absorbance, which is superior to most of the current reports (Figure 4c). [15,[33][34][35][36][37][38][39] High light absorption laid a sound foundation for high photothermal conversion. The temperature distribution and change of CNFAs under light irradiation from a solar simulating source were monitored using an infrared (IR) thermal imager.…”
mentioning
confidence: 99%
“…As a result, Chinese black ink as the solar absorber coating was required to be further stabilized by atomic layer deposition (ALD) technique to improve the interfacial adhesion to the substrate and prevent the ink dispersing into the water. [71] Beyond above report, a series of PDA coatings have been developed as the photothermal agents for various applications, including photothermal therapy, [101] photothermal antibacteria, [102] photothermal-assisted MD, [103] photo thermalassisted water evaporation, [104,105] and photothermal-assisted crude oil cleanup. [97][98][99] It is well known that the structure of PDA is similar to eumelanin in organism, and thus it would enable PDA coating with excellent light absorption ability.…”
Section: Black-carbon-based Coatingsmentioning
confidence: 99%